A Compact Flower‐Shaped Printed Monopole MIMO Antenna for Wideband Applications. Issue 11 (7th November 2019) - Nath, V.; Kumar, M.
Abstract: This paper presents a 2 × 1 flower‐shaped (FS) multiple‐input multiple‐output (MIMO) monopole antenna with enhanced bandwidth and compact dimensions for modern wireless wideband applications. The proposed FS‐MIMO antenna is formed by merging multiple ellipses, each of which has a different value of semimajor axis length and eccentricity. These ellipses are used to obtain resonances at different frequencies, which cumulatively give a wideband behavior. The antenna characteristics such as reflection coefficient ( S 11 ), peak gain, surface current distribution at different resonating frequencies, and 2‐D radiation patterns are investigated. The measured impedance bandwidth (for S 11 below—10 dB) of the implemented antenna is around 126% (2.52–11.12 GHz). The measured peak gain varies from 2.16 to 6.57 dB in the entire impedance bandwidth. Furthermore, the measured values of diversity performance parameters such as envelope correlation coefficient, diversity gain, total active reflection coefficient, and mutual coupling ( S 21 ) are found within their acceptable limit. The more compact dimensions of 22 × 24 mm 2 (or about 0.15λ0  × 0.16 λ0 ) as compared to the latest state‐of‐art along with the good diversity performance makes the proposed antenna a capable contender for antenna structures supporting wide impedance bandwidth wireless applications. The proposed antenna shows the good matching characteristics under various scenarios such as an extended ground plane, USB connector, and device housing (both vertical and horizontal). Key Points: The proposed antenna has a compact size and possesses large impedance bandwidth as compared to the previously proposed wideband antennas A good diversity performance in terms of ECC, DG, multiplexing efficiency, MEG, CCL and TARC is also shown by the proposed antenna The proposed antenna also shows good performance when placed horizontally and vertically near to a large metallic body